(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To find out the effectiveness of hydraulic distention of the shoulder joint capsule with frozen shoulder. Materials and Methods: This study was conducted from 14th July 2011 to 16th April 2012. A total of 79 patients from either gender with clinical and radiological (normal radiograph) diagnosis of frozen shoulder were included in the study. The procedure was performed in OPD. Results: Out of 79 patients, 40 (50.63%) were females and 39 (48.10%) were males with a ratio of 1.07:1. The mean age of the patients was 46.58 Â± 8.34 (range from 20-60 years). Out of these 79 patients, the procedure was effective in 74 (93.67%) patients. Conclusion: We conclude that the procedure is cost effective and improving the early range of movements with immediate relief of pain and other related symptoms. Key Words: Frozen shoulder, hydraulic distention, local anesthesia.